Building Information - Representation and Management: Fundamentals and Principles - Koutamanis, Alexander (TU Delft OPEN Books, 2019)
THIS IS THE FIRST EDITION, ONLY AVAILABLE ON REQUEST. PLEASE CONTACT Educationsupport THE 2ND EDITION IS AVAILABLE HERE The book presents a coherent theory of building information, focusing on its representation and management in the digital era. It addresses issues such as the information explosion and the structure of analogue building representations to propose a parsimonious approach to the deployment and utilization of symbolic digital technologies like BIM.